(untitled) (New York, 2009)
Fully updated to reflect changes in practice and policy, this new edition has been written to enhance excellence in teaching and learning design and support all involved in facilitating a world-class inclusive education. Offering plentiful and rich practical advice, this rigorous and sound introduction to the basics of teaching and learning in higher education draws together a large number of expert authors and a range of global case studies. A definitive guide for anyone working in higher education
Keywords: Giảng dạy Đại học,College teaching